Effects of daylily extract microcapsule on the quality and gel properties of steamed fish cake-a surimi-based product - Hongxun Wang; Jie Li; Tingting Liu; Yahong Han; Wenfu Hou; Yang Yi (Current Research in Food Science)
This study evaluated the effects of 0.95% daylily powder (m/m, 0.95%-DL), 0.5% daylily extract (m/m, 0.5%-DLE), and 0.5% daylily extract microcapsules (m/m, 0.5%-DLEMC) on the storage stability, gel properties, and microstructure of steamed fish cake. The results showed that 0.5%-DLEMC exhibited superior performance in maintaining product quality, significantly enhancing gel strength and reducing cooking loss. Detailed analysis revealed that both 0.5%-DLE and 0.5%-DLEMC promoted protein unfolding, leading to a structural transition from random coil to β-sheet, and increased the formation of disulfide and non-disulfide covalent bonds. These molecular interactions contributed to the formation of a more uniform and dense gel network, improving the overall gel properties. The overall findings suggest that the use of 0.5% DLEMC manifests potential in improving the quality of surimi-based products and would provide guidance for the implementation of DLEMC as an innovative additive in the food industry.